Stapled versus open haemorrhoidectomy: a prospective study - Mohammed, Serbin; Balachandran, Kavitha Jayanthi; Vineed, S.; Chisthi, Meer M. (International Surgery Journal, 2020)
Background: In this era of staplers and advanced techniques in surgery Milligan Morgan technique of open haemorrhoidectomy is still considered as gold standard procedure for symptomatic haemorrhoids. Stapler haemorrhoidectomy, even though it is practiced in many centres has not become common due to various factors. The present study was done to compare the efficacy, safety and advantages, if any, of the stapled haemorrhoidectomy to open procedure. Methods: This prospective study was performed in the department of general surgery, Government medical college, Thiruvananthapuram, Kerala over a period of 12 months from March 2015 to March 2016. Symptomatic patients with grade 3 and4 haemorrhoids were selected for the study. The patients were randomized into two equal groups of 20 each. Group A underwent conventional open haemorrhoidectomy and group B, stapled haemorrhoidectomy. Results: Mean operative time period for group A was 39.25 ±5.5 minutes and group B was 26.75±4.7 minutes. There was significant difference in the pain score between these procedures on first 3 post-operative days. There was also significant difference in group A and group B which was 6.55±1.099 and 3.55±0.759 days respectively for mean hospital stay and 9.90±1.651 and 5.70±0.865 days respectively for return to normal work. Conclusions: Stapler haemorrhoidectomy is associated with lower pain scores postoperatively and shorter duration of hospital stay with early return to work when compared to conventional open haemorrhoidectomy.